The Influence of Teachers' Public Speaking Ability on Students' Learning Concentration in Islamic Cultural History Subjects at Madrasah Tsanawiyah Asy-Syifa Balikpapan - Mochammad Dwiki Anugrah; Iskandar Yusuf (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to determine the effect of teachers' public speaking skills on students' learning concentration in the subject of Islamic Cultural History at Madrasah Tsanawiyah Asy-Syifa Balikpapan. Good public speaking skills are expected to improve the quality of delivering material and affect students' concentration levels in following the learning process. This study uses an associative quantitative method. The research sample consisted of 32 students randomly selected from classes taking Islamic Cultural History lessons. Data were collected through a questionnaire that measured the level of teachers' public speaking skills and students' learning concentration. The results of the analysis showed that there was a significant positive relationship between teachers' public speaking skills and students' learning concentration. This indicates that the better the teacher's public speaking skills, the higher the students' learning concentration on the subject. Based on these findings, it is recommended that teachers improve their public speaking skills to create a more interesting and effective learning atmosphere, in order to increase students' concentration and learning motivation.